2014
DOI: 10.1007/s13197-014-1655-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of taro mucilage and fat levels in sliced breads

Abstract: Bread is one of the most commonly consumed foods, and much ongoing research is aimed at meeting the demand for higher quality bread products in terms of greater volume and softness with characteristic flavor, aroma and color. The goal of the present study was to optimize the amounts of lyophilized taro mucilage and hydrogenated vegetable fat added to sliced bread formulations to improve the physical characteristics of the bread while reducing lipid levels and maintaining good sensorial quality. For the analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
(28 reference statements)
0
5
0
1
Order By: Relevance
“…Moreover, the gelatinization of starch also reduces the presence of fat because the retardation of water is transferred to the starch granules [ 68 ]. In a study by Nagata et al [ 69 ], physical, chemical, and sensory analyses of bread slices were carried out after the addition of taro mucilage. It was observed that bread containing taro mucilage showed excellent softness and sensorial properties.…”
Section: Application Of Taro Mucilagementioning
confidence: 99%
“…Moreover, the gelatinization of starch also reduces the presence of fat because the retardation of water is transferred to the starch granules [ 68 ]. In a study by Nagata et al [ 69 ], physical, chemical, and sensory analyses of bread slices were carried out after the addition of taro mucilage. It was observed that bread containing taro mucilage showed excellent softness and sensorial properties.…”
Section: Application Of Taro Mucilagementioning
confidence: 99%
“…falling number of 369 s, stability greater than 20 minutes, water absorption of 56.4 g 100 wet gluten and 9.4 g -1 100 dry gluten; plus the addition of hydrogenated fat (15.8 g -1 kg ) and freeze dried taro mucilage (7.3 g -1 kg ) following the recommendation of (Nagata et al, 2015).…”
Section: Description Of the Experimental Data Or Materials Or Raw Matementioning
confidence: 99%
“…Some hydrocolloids have effects that are similar to those of emulsifiers (Bárcenas & Rosell 2007;Ribotta et al, 2004), and taro mucilage is an example of a hydrocolloid with emulsifying power (Nagata et al, 2015). Mucilage is a gummy substance found in vegetables and is usually present in tropical roots and tubers; it is particularly abundant in taro (Huang et al, 2010;Nagata et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A mucilagem de taro desempenha papel de interesse na indústria de alimentos devido às suas propriedades como espessante, estabilizante, emulsificante e substituto de gordura em pães de forma (Nagata et al, 2014;Tavares et al, 2011). Porém, para melhor ação desse aditivo natural, é interessante padronizar uma técnica de extração em que não haja impurezas que interfiram nas suas propriedades.…”
Section: Introductionunclassified